PELESTARIAN MAKANAN JEPA SEBAGAI DAYA TARIK WISATA GASTRONOMI DI KABUPATEN MAJENE - Mutiara Ulpa (Journal Peqguruang: Conference Series, 2025)
One of the traditional foods of the Mandar tribe in Majene Regency is Jepa. Jepa is a staple food that serves as an alternative to rice consumed by the Mandar people. Jepa can be a tourist attraction in gastronomic tourism due to its uniqueness and savory taste. The purpose of this research is to identify the components of gastronomic tourism found in Jepa and to analyze efforts for preservation and increasing the production of Jepa.The research method used is a qualitative descriptive method with data collection techniques including observation, literature study, interviews, and documentation study. The results of this research show that Jepa meets components of the principles of gastronomic tourism, thus having the potential to be developed as a gastronomic tourism attraction in Majene Regency.  Keywords: gastronomy, preservation, tourism